Students’ and Teachers’ Attitudes towards the Role of Note-taking in Enhancing Learners’ Autonomy Case of Master One Students of English at the University of Souk-Ahras - Douaa MAHDJOUR (My University, 2023)
Abstract The problem within university students is learning dependency. The purpose of this study is to investigate students’ and teachers’ attitudes towards the role of the note- taking to develop learners' autonomy. In our research we have focused on fostering autonomy using note-taking strategy which has proved to be one of the most effective strategies in the learning process, we hypothesize that Students and teachers have a positive attitude towards the effective role of note-taking in enhancing learners' autonomy. To prove this hypothesis, a questionnaire has been designed and administered to 56 students chosen randomly from 96 first year master students in addition to a semi-structured interview was conducted with 4 teachers to gain more information about their opinions concerning the use of note- taking in fostering autonomy in learning. Results have shown a positive attitude from both teachers and students towards the note-taking strategy as an effective tool to foster autonomous learning. ------------- الملخص المشكلة داخل طلاب الجامعة هي التبعية. قد يكون السبب وراء هذه المشكلة مرتبطًا بعدم الوعي بأهمية التعلم المستقل. ان الهدف من الدراسة الحالية هي البحت في مواقف الطلاب والمعلمين تجاه دور تدوين الملاحظات في تطوير استقلالية المتعلمين. ركزنا في بحثنا على تعزيز الاستقلالية باستخدام استراتيجية تدوين الملاحظات التي أثبتت أنها واحدة من أكثر الاستراتيجيات فعالية في عملية التعلم، ونفترض أن الطلاب والمعلمين لديهم موقف إيجابي تجاه فعالية تدوين الملاحظات في تعزيز استقلال المتعلمين. لإثبات هذه الفرضية، تم اجراء استبيان على 56 طالبًا تم اختيارهم عشوائيًا من 96 طالب ماجستير في السنة الأولى بالإضافة إلى مقابلة شبه موجهة مع 4 معلمين للحصول على مزيد من المعلومات حول آرائهم فيما يتعلق باستخدام تدوين الملاحظات في تعزيز الاستقلالية في التعلم. أظهرت النتائج موقفًا إيجابيًا من كل من المعلمين والطلاب تجاه استراتيجية تدوين الملاحظات كأداة فعالة لتعزيز التعلم المستقل ------------ Résumé Le problème chez les étudiants universitaires est la dépendance. La raison de ce problème peut être liée au manque de sensibilisation à l'importance de l'apprentissage indépendant. L'objectif de la présente étude est d'étudier les attitudes des élèves et des enseignants envers le rôle de la prise de notes dans le développement de l'autonomie des apprenants. Dans notre recherche, nous nous sommes concentrés sur l'amélioration de l'indépendance en utilisant la stratégie de prise de notes, qui s'est avérée être l'une des stratégies les plus efficaces dans le processus d’apprentissage Nous émettons l'hypothèse que les étudiants et les enseignants ont une attitude positive envers l'efficacité de la prise de notes. Dans la promotion de l'autonomie des apprenants. Pour étayer cette hypothèse, 56 étudiants sélectionnés au hasard parmi 96 étudiants de première année de master ont été interrogés ainsi qu'un entretien semi-directif avec 4 enseignants afin d'obtenir plus d'informations sur leurs opinions concernant l'utilisation de la prise de notes dans la promotion de l'autonomie dans les apprentissages. Les résultats ont montré une attitude positive des enseignants et des élèves envers la stratégie de prise de notes comme outil efficace pour promouvoir l'apprentissage autonome.